A multi-method analysis of incompleteness in behavioral treatment of contamination-based OCD. (March 2019) - Mathes, Brittany M.; Kennedy, Grace A.; Wilver, Natalie L.; Carlton, Corinne N.; Cougle, Jesse R.
Abstract: Contamination fear and washing compulsions are among the most common symptoms of obsessive compulsive disorder (OCD). Though these symptoms have traditionally been viewed as being driven by a desire to avoid harm, recent research has highlighted the importance of feelings of incompleteness (INC) or not-just right experiences (NJREs) in this symptom dimension. However, no study to date has examined the extent to which INC/NJREs may be associated with treatment response for contamination symptoms. The current study used a multi-method approach to examine the role of INC/NJREs in treatment of contamination symptoms. Participants ( n = 88) with elevated contamination symptoms, half of whom met for an OCD diagnosis, engaged in three sessions of exposure and response prevention (ERP) targeting contamination fears, and completed self-report and in vivo measures of INC/NJRES and contamination symptoms. ERP was associated with significant reductions in INC/NJREs. Further, changes in INC were associated with changes in contamination symptoms, independent of changes in harm avoidance. Greater discomfort in response to an in vivo NJRE task at pre-treatment predicted poor treatment response, though a self-report measure of INC did not predict response. These findings provide novel evidence for the importance of INC/NJREs in contamination-based OCD and its treatment. Highlights: Behavioral treatment for contamination OCD was associated with reductions in incompleteness and 'not just right' experience. Pre-treatment response to in vivo task predicted worse treatment outcome. Changes in incompleteness were uniquely associated with changes in contamination symptoms.